Leiomyosarcoma of Pancreas: A Rare Malignancy - Nasrollahi, Hamid; Omidvari, Shapour; Mokhtari, Maral; Hamedi, Seyed Hassan; Ansari, Mansour; Mohammadian Panah, Mohammad; Ahmadloo, Niloofar; Mosalaei, Ahmad (Reports of Radiotherapy and Oncology, 2016)
Introduction: Pancreatic leiomyosarcoma is a rare tumor and its clinical course and treatment is not well described. Case Presentation: This paper reports on a 57-year-old male, who presented epigastric pain and had a 12-cm pancreatic tail leiomyosarcoma. He received adjuvant radiotherapy after complete tumor resection. He developed local recurrence 11 months later and received no further treatment. He died after 3 months. Conclusions: The literature search revealed that pancreatic leiomyosarcoma has a variable clinical course and behavior.